2020
DOI: 10.1038/s41598-019-56811-2
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional reconstruction of the feeding apparatus of the tick Ixodes ricinus (Acari: Ixodidae): a new insight into the mechanism of blood-feeding

Abstract: The different components of the mouthparts of hard ticks (Ixodidae) enable these parasites to penetrate host skin, secrete saliva, embed, and suck blood. Moreover, the tick's mouthparts represent a key route for saliva-assisted pathogen transmission as well as pathogen acquisition from blood meal during the tick feeding process. Much has been learned about the basic anatomy of the tick's mouthparts and in the broad outlines of how they function in previous studies. However, the precise mechanics of these funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 17 publications
0
18
0
1
Order By: Relevance
“…The actions of cholinomimetic drugs have been tested across several species in the ixodid family 16 , 63 , 64 , and current models suggest that pilocarpine-mediated salivation is linked to putative mAChR activation in tick synganglion, that subsequently stimulates an unidentified secreto-motor nerve directly innervating the SG 33 . In addition, our recent study also showed that pilocarpine induces tick chelicera movement, suggesting that this drug may have a complex effect on Ixodes feeding behaviour 65 . The hypothesis that mAChR may be a cholinoceptive site for salivation has also been confirmed by effectively blocking pilocarpine-mediated fluid secretion with atropine, a typical mAChR-A antagonist 33 .…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The actions of cholinomimetic drugs have been tested across several species in the ixodid family 16 , 63 , 64 , and current models suggest that pilocarpine-mediated salivation is linked to putative mAChR activation in tick synganglion, that subsequently stimulates an unidentified secreto-motor nerve directly innervating the SG 33 . In addition, our recent study also showed that pilocarpine induces tick chelicera movement, suggesting that this drug may have a complex effect on Ixodes feeding behaviour 65 . The hypothesis that mAChR may be a cholinoceptive site for salivation has also been confirmed by effectively blocking pilocarpine-mediated fluid secretion with atropine, a typical mAChR-A antagonist 33 .…”
Section: Discussionmentioning
confidence: 92%
“…We also cannot exclude the possibility of the mAChR role as an autoreceptor, where the presynaptic mAChR(s) is under the feedback control like the cases shown in insect 76 . Furthermore, systemic effects of injected drugs should be taken into account, since fluid ingestion by ticks involves several primary tick feeding apparatus 65 . In addition we were interested to see if cholinergic synapses within type I acini are active during tick desiccation.…”
Section: Discussionmentioning
confidence: 99%
“…As recently supported by mechanistic studies [27], feeding of ixodid ticks begins with the secretion through inserted mouthparts of cement salivary proteins [28]. Cement is a complex substance secreted by most ticks of the family Ixodidae including Rhipicephalus spp.…”
Section: Introductionmentioning
confidence: 95%
“…This early interruption of neuromuscular activity may play a key role in isoxazoline blocking of the transmission of tick-borne pathogens. An animated model of the feeding apparatus of Ixodes ricinus has highlighted ways in which tick feeding and salivation processes are regulated by neuromuscular activity [ 27 ]. First, the pharyngeal valve opens and the pharynx dilates to imbibe blood, then the valve closes and the pharynx contracts, pushing the bloodmeal into the midgut.…”
Section: Discussionmentioning
confidence: 99%
“…A decrease in blood intake could reduce the signal needed to prepare these pathogens for transmission. Additionally, muscles attached to the salivarium are likely involved in the expulsion of saliva into the host, such that paralysis of these muscles via isoxazoline exposure would potentially further reduce the risk of pathogen transmission [ 27 ]. While our study did not directly measure neuromuscular potential or study the muscles involved in the feeding apparatus, isoxazoline compounds act by blocking insect and acarine GABA- and glutamate-gated chloride channels, providing a basic mechanism for disrupting the transmission of pathogens [ 30 32 ].…”
Section: Discussionmentioning
confidence: 99%